Mechanism Design and Kinematics Analysis of a Hybrid-driven Waist Rehabilitation Robot - Yin Guangcai; Zi Bin; Chen Qiao; Li Yuan (Jixie chuandong)
A cable-pneumatic-muscle hybrid-driven waist rehabilitation robot is designed for human waist and gait rehabilitation training.The presented data and curves indicate that the state of motion of human torso during normal walking and the rehabilitation robotics fundamental functions are confirmed.According to these,the structure of the rehabilitation robot that employed the double parallel mechanism is designed.The cable- driven parallel mechanism is chosen to drive the human lower limb,and the pneumatic muscle（PM） is chosen to twist the human waist.The adaptability and safety of the rehabilitation robot is enhanced by synthesized the features of the two actuators.The inverse kinematics are solved by using the closed-vector-circle method,and the velocity Jacobian matrix is established.In addition,the rehabilitation robotics kinematics model and the PM element thermodynamics model are established in view of the parameters of different trainers is diverse.Then the kinematics character of cables and PM during the normal walking are obtained through numerical simulation,and the force variation trend of PM elements is also simulated to verify the feasibility of mechanism.